KARAKTERISTIK UMUR PAHAT PADA PROSES MILLING TERHADAP PEMESINAN KERING AISI 4140 - Harianja, Ivan Andri; Yunus, Surya Murni (Jurusan Teknik Mesin, Fakultas Teknologi Industri, Institut Teknologi Medan (ITM), 2017)
Tool life is a machining data that is very important in machining planning. Characteristics of tool life is a function of the thickness of the chips, temperature and flow velocity of the debris. If the thickness of the flakes is greater, the temperature will be higher while the flow rate of the flakes will be lower than the cutting speed so that the tool wear / tool life is obtained. The research was conducted by observing the effect of cutting conditions, where the cutting speed was varied while other cutting conditions, such as feeding motion, infeed depth and fixed cutting time. The purpose of this study was to determine the HSS tool life with AISI 4140 steel. 755 m / min, f = 0.5 mm / put, a = 0.5 mm, that the tool wear (Vb) obtained is 0.325 mm, the value can be said that the tool wear / tool life limit has been reached, because according to ISO 3685 tool life wear limit is 0.3 mm.